Peran Komunikasi Interpersonal Single Mother Bekerja dalam Membangun Kelekatan dengan Anak di Lingkungan Perumnas Urung Kompas Rantau Prapat - Anggi Damayanti; Solihah Titin Sumanti (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This study explores the significance of interpersonal communication in the relationship between single working mothers and their children in a residential setting. Employing qualitative descriptive methods, the study utilizes primary and secondary sources of data through interviews and observations. Data analysis is conducted through conclusion writing, data presentation, and data minimization. The findings suggest that effective communication between single mothers who work and their children has a substantial impact on their relationship. Parent-child relationships are key factors influencing child behavior. A balanced approach to parenting ensures that healthy persistence does not result in a lack of compassion in the child, and vice versa. Children's behavior is shaped by their surroundings, with parents being the closest elements. Thus, it is essential for single mothers who also play the role of a father to set good examples through prioritizing their children's interests, promoting healthy interpersonal communication, supervising their children, and creating an environment in which children feel secure enough to open up to their parents. Overall, this study highlights the importance of effective communication in building strong parent-child relationships in single-mother households.